2016
DOI: 10.1002/asia.201600698
|View full text |Cite
|
Sign up to set email alerts
|

Metal–Organic Gel Material Based on UiO‐66‐NH2 Nanoparticles for Improved Adsorption and Conversion of Carbon Dioxide

Abstract: Metal-organic frameworks (MOFs) including the UiO-66 series show potential application in the adsorption and conversion of CO2 . Herein, we report the first tetravalent metal-based metal-organic gels constructed from Zr(IV) and 2-aminoterephthalic acid (H2 BDC-NH2 ). The ZrBDC-NH2 gel materials are based on UiO-66-NH2 nanoparticles and were easily prepared under mild conditions (80 °C for 4.5 h). The ZrBDC-NH2 -1:1-0.2 gel material has a high surface area (up to 1040 m(2)  g(-1) ) and showed outstanding perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 42 publications
(50 reference statements)
1
37
0
Order By: Relevance
“…The mesopore size distributions are depending on the size of the primary particles, and the larger size of the primary particles should result in the larger mesopore size. In addition, it has been reported that the crystallization and grain growth behavior of UiO‐66 are critically influenced by the solvent composition . In this case, therefore, it is considered that the grain growth is more significantly impeded in the solvent containing PPG than in the solvent without PPG, and as a result, the difference in the mesopore size distribution was observed.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The mesopore size distributions are depending on the size of the primary particles, and the larger size of the primary particles should result in the larger mesopore size. In addition, it has been reported that the crystallization and grain growth behavior of UiO‐66 are critically influenced by the solvent composition . In this case, therefore, it is considered that the grain growth is more significantly impeded in the solvent containing PPG than in the solvent without PPG, and as a result, the difference in the mesopore size distribution was observed.…”
Section: Resultsmentioning
confidence: 98%
“…However, in general, the high crystallization tendency of MOFs impedes such uniform gelation. Opaque gels composed of aggregated crystallites coarse enough to scatter the visible light thus have been obtained in previous works . Macroporous structure is not controllable in such cases because the formation of macropores relies on the uncontrolled aggregation of coarse crystallites.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…4751 For example, the synthesis of UiO-66-(COOH) 2 from ZrCl 4 in water proceeds through the formation of a white gel. 48,49 Gelation during the synthesis scale-up of UiO-66, using zirconyl chloride octahydrate (ZrOCl 2 ·8H 2 O) as precursor, was also reported by Ragon and coworkers.…”
Section: Introductionmentioning
confidence: 99%
“…50 Finally, Liu et al described a MOF gel synthesized from an ethanol–DMF mixture using 2-aminoterephthalic acid and ZrCl 4 . 51 However, detailed investigations into the synthesis or structure of such gels are sparse; there are no reports on formation of crystalline monolithic materials or hierarchically porous architectures from these gels.…”
Section: Introductionmentioning
confidence: 99%